The quick and the dead [videorecording (DVD)] - Stone, Sharon, 1958-; Hackman, Gene; DiCaprio, Leonardo; Crowe, Russell, 1964-; Sinise, Gary (Columbia TriStar Home Video, 2000)
This reinvention of the American Western is a wild, sexy shoot-out studded with action, suspense and offbeat humor.